The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/md.0000000000034119
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound diagnosis of fetal giant pericardial cyst: A case report

Abstract: Rationale: We describe 1 case of fetal giant pericardial cyst was diagnosed by fetal echocardiography in the second trimester, and the changes of the cyst were recorded by follow-up observation in the late trimester and after birth. We then review and discuss the knowledge about its diagnosis and treatment. Patient concerns: A 34-year-old pregnant woman was referred to our hospital because of a diagnosis of a fetal pericardial effusion at 22 5/7 weeks at another hospital. Diagnosis: Fetal echocardiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thymic cysts, which are associated with the migration of thymic tissue to the anterior mediastinum during embryonic development, tend to occur in this region. Pericardial cysts are closely associated with the pericardial sac, and account for approximately 7% of mediastinal cysts ( 11 ). They arise from certain embryonic structures in the cephalic and lateral plates of the mesoderm that failed to fuse completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymic cysts, which are associated with the migration of thymic tissue to the anterior mediastinum during embryonic development, tend to occur in this region. Pericardial cysts are closely associated with the pericardial sac, and account for approximately 7% of mediastinal cysts ( 11 ). They arise from certain embryonic structures in the cephalic and lateral plates of the mesoderm that failed to fuse completely.…”
Section: Discussionmentioning
confidence: 99%
“…They arise from certain embryonic structures in the cephalic and lateral plates of the mesoderm that failed to fuse completely. These cysts are commonly located in the middle mediastinum at the base of the heart ( 11 ). Similarly, our study found that most pericardial cysts were located in the right septal angle region.…”
Section: Discussionmentioning
confidence: 99%